Corticosteroid‐induced glaucoma in pediatric patients with hematological malignancies. Issue 12 (6th September 2019) - Sugiyama, Minako; Terashita, Yukayo; Hara, Kazuya; Cho, Yuko; Iguchi, Akihiro; Chin, Shinki; Manabe, Atsushi
Abstract: Background: Corticosteroids, especially dexamethasone, play a critical role in chemotherapy for pediatric hematological malignancies. We previously observed that patients with complaints of headache or photophobia during corticosteroid administration had high intraocular pressure (IOP). Procedure: We measured IOP during corticosteroid administration in 15 patients with acute leukemia or lymphoma undergoing treatment at our institution from January 2016 to December 2018. IOP was measured by an ophthalmologist within seven days of the initiation of standard dose of corticosteroid, which was defined as 60 mg/m 2 /day for prednisolone and 10 mg/m 2 /day for dexamethasone. Results: Fifteen patients received 52 courses of chemotherapy containing corticosteroids. IOP exceeded 21 mmHg among 13 patients in 28 courses. Twelve of the 13 patients were administered topical treatment, and six of the 12 patients needed additional diuretic agents. IOP during the chemotherapy courses containing dexamethasone was significantly higher compared with IOP during the chemotherapy courses containing prednisolone. Only two patients complained of symptoms, such as headache and photophobia, and one of the two patients underwent trabeculotomy. Funduscopic findings were normal in all patients. There was a dose‐associated decrease in IOP with reduction of dexamethasone dose. Conclusions: IOP should be measured during administration of substantial corticosteroid doses even in patients with no symptoms. Further investigations regarding the level of IOP for intervention need to be conducted.